Modelo lógico para análise de políticas públicas em perspectiva histórica - Cleandro Krause (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper proposes a hypothetical representation of a policy seen in historical perspective. The modernization of the city of Porto Alegre, in the south of Brazil, from the end of the 1920s until 1937 was the empirical object of the author's PhD thesis in Urban and Regional Planning. Here we highlight its methodological framework, namely a logical model developed at the Institute for Applied Economic Research (Ipea), here applied for the outline of an urban circulation problem/program. Such configuration includes the three components of the logical model: an explanation of the problem and the program's basic references; the program's structuration towards the achievement of desired outcomes; and the identification of relevant factors of context. We sought evidence for the representation of the three components in historical sources, which have also supported a vulnerability analysis of the program's logical model. Such analysis permits to explain why the program's structuration would not have allocated the most adequate treatment to the problem's causes. We finally present considerations on retrospective uses of the logical model, which may aggregate knowledge on concrete acts of policy implementation in the past, in order to provide more robust explanations of problems that persist and must be tackled by new programs in the present.
Keywords: O18; 330; urban problems; urban circulation; logical model